Epibionts on Hydraena species (Coleoptera: Hydraenidae) from high mountain rivers of Pyrenees (Ordesa and Monte Perdido National Park), with the description of a new species - Fernández-Leborans, Gregorio; Valladolid, María; Arauzo, Mercedes; Millán, Andrés; Gabilondo, Regina; Gallardo, Manuela; Jiménez, Luis; Ramírez-Ballesteros, Mireya (Zootaxa, 2017)
Macroinvertebrate samples collected during spring-summer 2013 in high mountain rivers of the Ordesa and Monte Perdido National Park (Pyrenees) contained several Hydraena species (Coleoptera: Hydraenidae) where we found two genera of suctorian ciliates as epibionts: Tokophrya and Discophrya. The individuals of the genus Tokophrya probably belong to species Tokophrya stenostyla, being the first time that this species is observed attached on arthropods. Suctorians of the genus Discophrya were identified as a new species called Discophrya ordesae sp. n. The presence and abundance of epibionts was discussed in the frame of the biological and ecological characteristics of the species of Hydraena where they were found.